(untitled) (Nigerian Journal of Technology, 2017)
The compaction and consolidation characteristics of lateritic soils in Ikole area of Ekiti State were investigated. The investigation was carried out through laboratory tests on disturbed and undisturbed soil samples obtained from three borings (BH1, BH2, and BH3) of Holy Apostolic Nursery/Primary School, Ootunja, Ikole Local Government Area (L.G.A.) of Ekiti State Southwest, Nigeria. The soils are all lateritic and mostly fine-grained. Compaction tests indicate maximum dry densities of 2.05Mgm-3, 1.78Mgm-3, and 1.69Mgm-3 at optimum moisture contents of 14.3%, 20.7% and 19.6% for soil samples obtained from BH1, BH2 and BH3 respectively. Compression indices (Cc) obtained from oedometer tests are 0.04816, 0.03820 and 0.04318 while the calculated coefficients of volume compressibility (mv), are 1.308*10-4, 1.065*10-4 and 1.093*10-4 m2kN-1 for samples in BH1, BH2 and BH3 respectively. The unsoaked California Bearing Ratio (CBR) value at 2.5 mm penetration ranges from 42.10% to 92.40% and CBR value at 5.0 mm penetration ranges from 52.70 to 89.10% indicative of good materials for road subgrade, sub-base and base courses. http://dx.doi.org/10.4314/njt.v36i2.3